Explorations of predictors for parametrial invasion and how it affects treatment strategy for bulky cervical cancer - Yang, Jing; Ji, Jianan; Ni, Xiao; Li, Yang; Chen, Ting; Zhang, Jing; Qiu, Jiangnan; Luo, Chengyan (Frontiers in Oncology, 2025)
ObjectivesThe treatment of bulky cervical cancer (BCC) remains challenging owing to poor local control and susceptibility to distant metastasis. The study aimed to identify the factors that affect the development of parametrial invasion (PMI) and evaluate their association with different treatment modalities for BCC.MethodsThe retrospective study enrolled 462 women with BCC treated at our center between January 2010 and June 2023. Logistic regression was utilized to analyze the factors influencing PMI. Kaplan-Meier method and Cox proportional hazard model were employed for survival analyses.ResultsFIGO stage III-IV and primary tumor volume > 16 cm³ were identified as independent predictors for PMI in BCC, with ORs of 6.45 (95% CI 2.43-18.01) and 2.11 (95% CI 1.25-3.61), respectively. Multivariate Cox regression analysis demonstrated that the presence of PMI was associated with poorer progression-free survival (PFS) (HR 1.72, 95% CI 1.02-2.9), but exerted no significant effect on cancer-specific survival (CSS) (HR 0.86, 95% CI 0.37-2.0). The patients with FIGO stage I-II disease and no PMI who received radical surgery and adjuvant radiotherapy (RS and ART) presented improved PFS than those receiving concurrent chemoradiotherapy (CCRT), whereas CSS was unaffected. The cases at FIGO stage I-II with PMI exhibited no significant difference in PFS or CSS between receiving different treatments. No discernible difference in the incidence of grade ≥ 3 radiotherapy-related adverse events and quality of life was observed between treatment groups at 3- and 6-month post-treatment.ConclusionsBCC patients with FIGO stage III-IV and tumor volume > 16 cm3 were more susceptible to PMI. RS and ART improved PFS in patients with FIGO stage I-II disease and no PMI without increasing risks for serious adverse events and impairing the patients’ quality of life.